Docosahexaenoic acid (DHA) Supplementation During Pregnancy Reduces the Risk of Preterm Birth in Threatened Preterm Labor. The Multicenter Randomized Controlled Trial - Phattharachindanuwong W; Chaiyarach S; Komwilaisak R; Saksiriwuttho P; Duangkum C; Kongwattanakul K; Kleebkaow P; Waidee T; Pongsamakthai M; Chantanavilai S; Srisataporn T (International Journal of Women's Health)
Wiphawi Phattharachindanuwong,1 Sukanya Chaiyarach,1 Ratana Komwilaisak,1 Piyamas Saksiriwuttho,1 Chatuporn Duangkum,1 Kiattisak Kongwattanakul,1 Pilaiwan Kleebkaow,1 Termtem Waidee,1 Manasicha Pongsamakthai,2 Sathida Chantanavilai,2 Tunyatorn Srisataporn2 1Department of Obstetrics and Gynecology, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand; 2Department of Obstetrics and Gynecology, Khon Kaen Hospital, Khon Kaen, ThailandCorrespondence: Wiphawi Phattharachindanuwong; Sukanya Chaiyarach, Department of Obstetrics and Gynecology, Faculty of Medicine, Khon Kaen University, Khon Kaen, 40000, Thailand, Tel +66869077662 ; +66836760565, Email wiphawi.beer@gmail.com; sukancha@kku.ac.thBackground: Threatened preterm labor is a common reason for hospital admission, and DHA supplementation may lower the risk of preterm labor.Objective: To compare the rates of premature birth between individuals with threatened preterm labor who received DHA and those who did not.Methods: In this multi-center randomized controlled trial, the sample size was calculated to be 60 participants. Pregnant individuals who experienced threatened preterm labor at 24 to 34 weeks gestation were given either 1000 milligrams of DHA daily or no DHA supplement. The criteria for inclusion consisted of singleton pregnancies that had been diagnosed with threatened preterm labor, with no cervical change present. DHA supplementation was initiated when threatened preterm labor was diagnosed and continued until 37 weeks of gestation or until delivery, whichever occurred first. The main outcome was to compare the rates of premature births between the two groups. Moreover, we intended to evaluate the side effects of the DHA supplement along with the outcomes for neonates.Results: Sixty-one pregnant individuals were enrolled and randomly assigned to two groups. Group 1 consisted of 30 participants, each receiving a daily intake of 1,000 milligrams of DHA supplement. Group 2, comprising 31 individuals, did not receive any supplemental DHA. The rate of preterm birth was 23.33% (7/30) and 25.81% (8/31) for the participant group receiving DHA and not receiving DHA, respectively, with a p-value of 0.82. The rate of low-birth-weight neonates was 13.33% (4/30) and 19.35% (6/31) for the participant group receiving DHA and not receiving DHA, respectively, with a p-value of 0.73. The overall results did not show any statistically significant differences. In addition, the rates of cesarean sections, peripartum infections, early postpartum hemorrhage, and NICU admissions did not show significant differences between the two groups.Conclusion: Taking DHA supplements after a diagnosis of threatened preterm pregnancy does not decrease the actual rates of early or late preterm births. To reduce the risk of premature birth, DHA should be taken from the beginning of pregnancy, with a recommendation to start in the first trimester. This should ideally start in the second trimester, no later than around 20 weeks of gestation, and should continue until childbirth or approximately 37 weeks of gestation.Clinical Trial Registration: https://register.clinicaltrials.gov/.Clinical Trials: gov; ID: NCT06302023.Keywords: docosahexaenoic acid, DHA, preterm birth, threatened preterm labor, omega-3 polyunsaturated fatty acids, pregnancy nutrition